(untitled) (Economics and region, 2025)
One of the most pressing and acute problems of modern society in Ukraine is the issue of discrimination. The main aspects that it covers are, in particular, restrictions on a person on such grounds as gender, race, origin, language and culture, health status, age, nationality, political beliefs and religion, as well as many others. This problem is most noticeably felt in the labor sphere, since discrimination on various grounds has a great impact on equality in employment opportunities, working conditions, equal pay and prospects for professional growth. The purpose of the work is to analyze the sectoral principles of labor law, study the problems of discrimination in the labor sphere, develop views on this basis, crystallize positions to ensure equality and freedom of labor. The study of the problem is studied using a system of methods of scientific knowledge: induction, deduction, comparison, systemic method, generalization.The article is devoted to the study of the peculiarities of labor relations, taking into account the key industry principles of labor law. The authors focus their attention on the issues of non-discrimination in the sphere of labor, freedom of labor as the basis for stable labor relations. The analysis of these issues is examined, among other things, in the light of state policy in Ukraine regarding non-discrimination in the labor sphere, as an effective and fundamental basis for respecting human rights, and participants in labor relations in particular. In the article, young scientists highlight interesting views on the mentioned problem, which is the subject of research in the work.The authors conclude that these can be positive actions, or so-called positive discrimination, aimed at supporting socially vulnerable groups of the population, which will ensure fairer employment conditions and contribute to the development of an inclusive society. However, effective counteraction and prevention of discrimination is possible only with a comprehensive approach to its solution, which combines legal mechanisms, educational activities and positive actions.